2017
DOI: 10.2147/copd.s121943
|View full text |Cite
|
Sign up to set email alerts
|

Predicting high risk of exacerbations in bronchiectasis: the E-FACED score

Abstract: BackgroundAlthough the FACED score has demonstrated a great prognostic capacity in bronchiectasis, it does not include the number or severity of exacerbations as a separate variable, which is important in the natural history of these patients.ObjectiveConstruction and external validation of a new index, the E-FACED, to evaluate the predictive capacity of exacerbations and mortality.MethodsThe new score was constructed on the basis of the complete cohort for the construction of the original FACED score, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 21 publications
2
118
0
5
Order By: Relevance
“…Hereby, more patients are classified as “severe” disease using the BSI as compared to the FACED, and suggests that these scores measures different things; BSI is a severity assessment tool and FACED accurately predicts risk of death . Recently, Martinez‐Garcia published the E‐FACED, and incorporated the number of severe exacerbations in 1 year into the FACED. The E‐FACED showed a greater prognostic capacity for exacerbations and hospitalizations and its capacity to discriminate degrees of severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hereby, more patients are classified as “severe” disease using the BSI as compared to the FACED, and suggests that these scores measures different things; BSI is a severity assessment tool and FACED accurately predicts risk of death . Recently, Martinez‐Garcia published the E‐FACED, and incorporated the number of severe exacerbations in 1 year into the FACED. The E‐FACED showed a greater prognostic capacity for exacerbations and hospitalizations and its capacity to discriminate degrees of severity.…”
Section: Discussionmentioning
confidence: 99%
“…The disease severity was calculated using the validated BSI‐score and FACED score . In addition, the recently published E‐FACED score was also used to assess the disease severity . The BSI scoring system identifies individuals at risk of mortality, hospital admissions, and exacerbations, while the FACED score predicts the probability of all‐cause mortality after 5 years of follow up .…”
Section: Methodsmentioning
confidence: 99%
“…Prior exacerbations are also the strongest predictor of future exacerbations which explains why a number of studies have found FACED to be poorly predictive of future morbidity. 121123 For this reason the BSI is the preferred scoring system. At the time of writing, modifications of the FACED score to include exacerbations are undergoing evaluation.…”
Section: Sectionmentioning
confidence: 99%
“…The following data were collected: demographic data, clinical data (age at start of symptoms and diagnosis of BE, presence and habitual type of expectoration, scale of mMRC dyspnea, exacerbade la Rosa Carrillo et al tions and admissions during the previous year, Charlson Comorbidity Index); BE etiology; etiological tests performed; radiological extension of BE; microbiological data; spirometric data; severity of BE according to Bronchiectasis Severity Index (BSI), FACED, and E-FACED scores [8,15,16]; time spent in the emergency department, in the hospital ward, and in the HH. We also collected data on employment, salary, the need for sick leave of the patient during the exacerbation, and the need for sick leave of the caregiver.…”
Section: Variablesmentioning
confidence: 99%